The Effect of Diabetes Self Management Education Program on Self-Management Knowledge in Patients with Diabetes Milletus Type II - Habid Al Hasbi; Bambang Sudono Dwi Saputro,; Tri Handayani (Politeknik Karya Persada Muna, 2022)
Baground: Education is very important given to diabetes milletus patients to improve their health and prevent complications. One of the educations for diabetes patients is Diabetes Self Management Education (DSME). DSME is an ongoing process undertaken to facilitate knowledge of clients' skills and abilities to perform self-care. This study aims to determine the effect of the Diabetes Self Management Education program on knowledge of self-management in patients with type 2 diabetes. Method: This study used a Quasi Experiment research method with a two group pre-post test control design conducted in April 2021. The sampling technique used purposive sampling with a sample of 36 people divided into 18 treatment groups received the DSME program and 18 control groups received education from the Puskesmas program. The instrument used is a questionnaire. Results: Contains research results that are written directly to answer the problem and discuss the results. Conclusions: The results showed that the P value of the Independent T Test for knowledge was 0.000 < 0.05, which means that there was a significant difference in knowledge between the control group and the treatment group Keywords: Diabetes self management education, knowledge